Imagens negociadas : retratos de família pelas lentes do estúdio Foto Klos nas décadas de 1930 e 1940 em Panambi - RS - Ribeiro, Carmem Adriane (2015)
This research paper discusses about the photographic production of the Photo Klos studio in Panambi (RS) in the 1930s and 1940s. Founded in 1913 in Panambi in the Northwest region of Rio Grande do Sul by immigrant Wilhelm Adam Klos, the studio remains as venture family until the present day, accounting a century of existence. The time frame established by the survey corresponds to the period when Frieda Doeth Klos took over the administrative activities and photographic studio. The research aimed to understand the moments that involved the negotiation for the production of family images consumption and circulation of photographs. Besides consulting the private studio collection - pictures and documents - interviews and reproduction of the images to used in the study produced by glass negatives were also made. Among the results of the research it is said that the photographs were used as a means of legitimizing the family outside the local society and the family and friends far away, seeing that the most of those portrayed in the being twentieth century, who besides be remembered, sought through images demonstrate their material progress.